2014
DOI: 10.1136/acupmed-2013-010509
|View full text |Cite
|
Sign up to set email alerts
|

Wet Needling of Myofascial Trigger Points in Abdominal Muscles for Treatment of Primary Dysmenorrhoea

Abstract: Primary dysmenorrhoea was significantly reduced 1 year after wet needling to MTrPs in the abdominal region and home stretching exercises, justifying further research with controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…Pain exacerbation caused by algometry on myofascial points considered as representing PD reaffirms that painful spots in torso muscles can frequently affect the function of surrounding internal organs, specially abdomen, thorax and pelvic floor muscles 11 . The reduction of pressure pain threshold and the presence of trigger points creates a vicious cycle, which includes harms to the activation of core muscles 14,25 , antalgic positions 13 and deficit in stabilization and balance 15 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Pain exacerbation caused by algometry on myofascial points considered as representing PD reaffirms that painful spots in torso muscles can frequently affect the function of surrounding internal organs, specially abdomen, thorax and pelvic floor muscles 11 . The reduction of pressure pain threshold and the presence of trigger points creates a vicious cycle, which includes harms to the activation of core muscles 14,25 , antalgic positions 13 and deficit in stabilization and balance 15 .…”
Section: Discussionsupporting
confidence: 52%
“…The connection between pain and postural control has already been described in acute 9 and chronic [10][11][12] musculoskeletal conditions, proving that changes in this system can cause disturbance on balance. Moreover, the adjustments in postural control can be affected by the adoption of antalgic postures 13 , the presence of myofascial trigger points 11 and paradoxical torso muscle contraction 12,14 , besides alterations in proprioception 8,15 .…”
Section: Introductionmentioning
confidence: 91%
“…There may also be additional mechanisms by which acupuncture-like treatments can relieve primary dysmenorrhoea; for example, by inactivation of myofascial trigger points on the abdomen using wet needling. 39 Overall, trial quality was low, which provides several caveats to causally linking the dosing used in these trials (either high-frequency, daily treatment or EA) directly to improved menstrual pain outcomes; there may be a reporting bias in the studies included in this review and some studies have used nonvalidated outcome measures such as effectiveness scores or CMSS scores, which incorporate multiple domains rather than just pain reduction.…”
mentioning
confidence: 99%
“…Moreover, the selection of clinical treatment sites is primarily related to the location of the myofascial trigger point. The clinical study by Huang et al [7,8] shows that the pain and related symptoms of PDM can be effectively alleviated in patients with the trigger point of abdominal myofascial pain and who receive local dry and wet acupuncture treatment at the trigger point. Li et al [9] and Xing [10] confirmed that rESWT can effectively alleviate the symptoms of chronic dysmenorrhoea.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%